Review of the Southeast Asian millipede genus Pacidesmus Golovatch, with the description of a new troglobitic species from southern China (Diplopoda: Polydesmida: Polydesmidae) - Golovatch, Sergei I.; Geoffroy, Jean-Jacques (Zootaxa, 2006)
The genus Pacidesmus is briefly reviewed, with all of its three species keyed, including the clearly troglobitic P. martensi sp. n. from two caves in Guizhou Province, China.